Pharmacological Treatment of Diabetic and Non-Diabetic Patients With Coronary Artery Disease in the Real World of General Practice - Rottura, Michelangelo; Molonia, Antonino; Giorgi, Domenico Antonio; Marino, Sebastiano; Scoglio, Riccardo; Pallio, Giovanni; Irrera, Natasha; Imbalzano, Egidio; Altavilla, Domenica; Squadrito, Giovanni; Squadrito, Francesco; Arcoraci, Vincenzo (Frontiers in Pharmacology, 2022)
Type 2 Diabetes Mellitus (T2DM) severely augments the probability of developing Coronary Artery Disease (CAD) and diabetic patients with CAD should be considered at very high cardiovascular risk. For this reason, the management of these patients need special attention by GPs. ADA and ESC guidelines recommend the use of aspirin, statins, beta blockers or RAAS inhibitors and at least one hypoglycemic agent belonging to the GLP-1 or SGLT2-i in diabetic patients with high/very high cardiovascular risk, regardless of the glycemic target. Our study provides information on the management of CAD patients with or without diabetes in clinical practice, showing that a “non-ideal” therapeutic approach was adopted in patients with diabetes and CAD. Results, highlighting also, the urgent need of a closer collaboration between the GPs, clinical pharmacologist and specialists in order to effectively improve adherence to guidelines and overall management of global cardiovascular risk in diabetic patients.